Nitric oxide and vascular disease - Shirodaria, C; Channon, K (2007)
Nitric oxide has a pivotal role in vascular homeostasis. It has a protective role because it suppresses abnormal proliferation of vascular smooth muscle after various diseases, including atherosclerosis and restenosis after vascular interventions (e.g. balloon angioplasty, stent deployment, bypass grafting). A reduction in the generation and bioavailability of nitric oxide is a critical step in the development of atherosclerosis, a disease of the arterial wall that underlies vascular disease. With cardiovascular diseases postulated to be the main cause of death globally within the next 15 years, increasing the understanding of the biology of atherosclerosis and the process of endothelial function may aid development of therapeutic strategies to reduce risk. © 2007 Elsevier Ltd. All rights reserved.